A Novel Method for IRFOC of Three-Phase Induction Motor under Open-Phase Fault - Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper investigates the vector control of a star-connected three-phase Induction Motor (IM) under stator winding open-phase fault. The used vector control method is based upon indirect rotor field-orientation concepts that have been adapted for this type of machine. Beside the implementation of this method in critical industrial applications, the proposed method in this paper can be used for vector control of unbalanced 2-phase or single-phase IM with two main and auxiliary windings. Simulation results are provided to show the operation of the proposed drive system.